ANEMIA DAN AKTIVITAS FISIK YANG RINGAN MEMPENGARUHI FAKTOR RISIKO DISMENORE PADA REMAJA PUTRI - Silvia Etika Sari; Martha Irene Kartasurya; Dina Rahayuning Pangestuti (Jurnal Kesehatan Masyarakat (Undip), 2018)
Dysmenorrhea often occurs on adolescents resulting in disrupted daily activities, especially learning activities at school. This research’s purpose is to analyze the relationship between anemia, physical activity, calcium and magnesium intake with adoslescents dysmenorrhea’s incidences in  Senior High School 4 Pekalongan. This research uses observational analytic with cross sectional design. Population are 442 adolescents of Senior High School 4 Pekalongan. Subjects are 80 people (5  from each class) chosen by respondents’ willingness to check for hemoglobin levels. Purposive Sampling technique is used. Dysmenorrhea’s incidences and pain degree data conducted by interview and numeric rating scale questionnaires. Anemia measurement conducted by Family Dr® strip test. Physical activity data conducted by recall for two consecutive days. Calcium and magnesium intake data conducted by Food Frequency Questionnaires. Data analyzed by Chi Square test. The results showed that 58.8% subjects suffered from anemia. 52,5% had very light physical activity. 77,5% consumed deficient calcium intake and 67,5% sufficient magnesium intake. There is a relationship between anemia (OR = 8.9; 95% CI: 2.6-30.7; p = 0.0001), very light physical activity (OR = 4.3; 95% CI: 1.3-13, 5; p = 0.019), deficient calcium intake (OR = 10.6; 95% CI: 3.1-35.3; p = 0.0001), and deficient magnesium intake (OR = 5.51; 95% CI: 1,1-26,0; p = 0,039) with the dysmenorrhea’s incidences in adolescents. It is suggested for adolescents to consume foods and beverages which contains calcium, magnesium and iron such as milk, nuts, tofu, tempeh, vegetables, especially spinach, broccoli, kale and doing extracurricular activities at school.